ANALYSIS OF BANK HEALTH LEVELS AND THE USE OF BRANCHLESS BANKING USING THE RGEC METHOD AT BANK KB BUKOPIN SYARIAH 2016- 2020 - Isa Zulfarida Arini (Universitas Airlangga, 2023)
A healthy bank is a bank that can carry out its functions optimally. Banks are intermediary institutionsand can foster public trust in innovative, efficient, and effective bank performance. The existence of anassessment of the soundness of the bank is very much needed for the stakeholders and to be used as abenchmark for optimizing performance as well as for detecting bankruptcy. The limitations of the publicin accessing banking services have led to branchless banking innovations to serve underprivilegedcustomers in remote parts of the country. The purpose of this study was to determine the soundness ofthe Bukopin Syariah KB bank using the RGEC (Riks Profile, Good Corporate Governance, Earnings,Capital) method and the use of branchless banking in 2016-2020. The method used in this study is adescriptive method with a quantitative approach. In this case, using the data object of Bank KB BukopinSyariah's financial statements for 2016-2020. The results of the study show that the health level of BankKB Bukopin Syariah in 2016-2020 received the predicate of being less healthy even though customersatisfaction in the use of branchless banking received a healthy predicate and this will have an impacton customer satisfaction and trust in the future. It can be said that the performance of the BukopinSyariah KB bank is still not optimal in various aspects of risk management.Keywords: Bank Health, RGEC, Branchless Banking, Bukopin Syariah